Properties of (Cd, Zn)S films deposited by DC co-sputtering - Mwakyusa, Lwitiko P. (Tanzania Journal of Engineering and Technology, 2023)
CdS thin film is commonly used as a buffer layer in most thin film solar cells. However, the buffer layer with less absorption in the visible region of the solar spectrum as well as that which provides perfect lattice matching with the absorbers is required. The incorporation of Zn in the CdS films can affect the structural and optical properties of the buffer layer. In this work, films of CdS and (Cd,Zn)S films were deposited by DC sputtering utilizing CdS and Zn targets. The concentration of Zn in the CdS was varied by changing the sputtering power of the Zn target. The influence of Zn concentration on the structural and optical properties of CdS films was investigated using X-ray diffraction (XRD) and Ultraviolet-Visible-Near Infrared (UV-VIS-NIR) spectroscopy, respectively. The XRD patterns confirm the growth preferential orientation of all films along the (002) plane. UV-VIS spectroscopy results indicate absorption edge shifts toward lower wavelength with an increase of Zn concentration in the CdS. The band gap evaluated by the Tauc plot of these films varied from 2.40 eV to 2.50 eV (0 ‰¤ x ‰¤ 0.14). The increased bandgap induces the density of localized states on the edge of the bandgap which leads to the increase in the Urbach tail width. Keywords: CdS thin film, Buffer layer, (Cd, Zn)S thin film, Co-sputtering